Manpower training programmes and employment stability - Zweimüller, Josef [Verfasser]; Winter-Ebmer, Rudolf [Verfasser] (My University, 1996)
"We evaluate Austrian labour market policy focusing on its possible effects upon recurrent unemployment. Without properly considering the selection processes for public training programmes, misleading results emerge. Taking the partizipation decision into account in a bivariate probit setting, Austrian manpower training programmes turn out to be a sort of 'catchingup': (i) disadvantaged and less motivated job-seekers are given priority in enrolment into training programmes, and (ii) participation in such courses improves employment stability significantly." (author's abstract, IAB-Doku) ((en)) Die Autoren evaluieren Weiterbildungsmassnahmen in Österreich im Hinblick auf die Stabilität anschliessender Beschäftigungsverhältnisse. Die Daten stammen aus den Jahren 1986 bis 1988. (IAB)
Keywords: G 1.2 Arbeitsmarkt; G 1.2.2.3 Beschäftigungsformen; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; I 2.2.1 Westeuropa; Arbeitsmarktpolitik; Erfolgskontrolle; Berufliche Weiterbildung; Umschulung; Beschäftigung; Dauer; Absolvent; Quantitative Angaben; Österreich; 1986-1988